1041 Assessment of physical health and fatigue among ancillary staff in a healthcare institution: a pilot study. (24th April 2018) - Lim, Dwee Wee; Lee, Lay Tin; Lee, Joseph
Abstract : Introduction: Ancillary staff in the hospital includes patient service associate, operating theatre attendant and executive who support healthcare workers in providing services to patient. This pilot study aims to assess the physical health and fatigue in this group of employees in the hospital to design an appropriate targeted intervention. Methods: This cross-sectional study collected data on ancillary staff who volunteered to participate in a 12 week exercise program. Data collected include demographics, anthropometric measurements, and exercise duration per week. Short physical performance battery (SPPD), timed-10 m walk test and grip strength for upper limb were assessed to derive score for aerobic fitness, muscular strength, balance and flexibility with maximum score of 100. Fatigue was assessed using Chalder Fatigue Scale which is able to assess both physical and mental fatigue. Total fatigue score was dichotomized to fatigued (>3) and non-fatigued employees (≤3). Results: There were a total of 78 participants, with mean age of 54.8 years. Majority were female (64.1%) and Chinese (48.7%). Of the participants, 12 (15.6%) were fatigued. Average body mass index (BMI) and waist-hip ratio (WHR) were 25.8 kg/m 2 and 0.87 respectively. In univariate analysis, age was not associated with any of the physical health score. Male had significantly higher aerobic fitness score compared to female (65.2 vs 85.7, p<0.001). Higher BMI is associated with lower aerobic fitness (p=0.001). All subscale for physical health were associated with physical fatigue, but only higher muscular strength is associate with lower mental fatigue score (p=0.038). In multivariate analysis, muscular strength and balance were independently associated with fatigued, OR of 0.94 (95% CI: 0.90 to 0.99) and 0.95 (95% CI: 0.92 to 0.99) respectively. Conclusion: Physical health and fatigue are related. Impact of physical health interventions on fatigue would require further studies.